Gastrointestinal Metastases From Primary Renal Cell Cancer: A Single Center Review - Maelle Rony; Jean-Philippe Ratone; Jochen Walz; Geraldine Pignot; Fabrice Caillol; Christian Pesenti; Mathilde Guerin; Slimane Dermeche; Serge Brunelle; Naji Salem; Cecile Vicier; Stanislas Rybikowski; et al. (Frontiers in Oncology, 2021)
Introduction: Digestive metastases (DMs) from renal cell cancer (RCC) are rare. Over the past decade, the overall survival of metastatic RCC (mRCC) has been improved by tyrosine kinase inhibitors (TKIs) and immune checkpoint inhibitors. The main objective of this study was to assess the incidence of metastases of the digestive tract in this new field of treatment. The secondary objectives were to evaluate the clinical characteristics, prognosis, treatments used for DMs, and median time between the diagnosis of RCC or mRCC and DMs.Materials and Methods: A retrospective analysis of data collected from all patients with mRCC between 2007 (the time of TKI was a standard of care) and 2019 was carried out at the Paoli-Calmettes Institute (Marseille, France). Computer research software using artificial intelligence (ConSoRe®) was used to identify patients and assess their characteristics.Results: Between January 2007 and December 2019, 11 out of 660 (1.6%) mRCC patients had metastases of the gastrointestinal tract. The median age was 62 years. Of the 11 patients, 81.8% experienced digestive bleeding or anemia. Only 2 patients were asymptomatic. The metastases were mainly duodenal (50%) and gastric (41.6%). The median time from cancer diagnosis and from metastatic disease to gastrointestinal metastasis was 4.3 years (3 months−19.2 years) and 2.25 years (0 days−10.2 years), respectively. Local treatment was performed in 38.5% of cases by endoscopy (60%), surgery (20%) and radiotherapy (40%) with success rates of 33, 100, and 50%, respectively. Etiological treatment was modified following the discovery of DM in 84.6% of the cases. The median survival was 1 year from the diagnosis of DM (13 days−9.4 years). Two patients were still alive 2.9 and 9.4 years after the diagnosis of DM.Conclusion: This is the largest monocentric retrospective analysis of DM in patients with RCC. It seems to be a rare and late event in the course of the disease. Local treatment combined with systemic treatment could improve survival. In the context of prolonged survival with the new based immunotherapy treatments in mRCC, we suggest that unexplained anemia or persistent digestive symptoms could be explored by endoscopy.